PENGARUH SUBSTITUSI TEPUNG AMPAS KELAPA DAN WORTEL (Daucus Carota L) TERHADAP NILAI ORGANOLEPTIK DAN NILAI GIZI COOKIES - Aminah, Sitti; tamrin, tamrin; Baco, Abdu Rahman (Jurnal Sains dan Teknologi Pangan, 2018)
ABSTRACT The purpose of this study was to determine the effect of coconut pulp and carrot flour formulations on the organoleptic properties and proximate values of cookies. This study used a Completely Randomized Design (CRD) with coconut pulp flour formulation, carrot flour and wheat flour ie. M0 (100% of flour wheat flour), M1 (40% ofcoconut pulp flour: 20% of carrot flour: 40% of wheat flour), M2 (35% of coconut pulp flour: 25% of carrot flour: 40% of wheat flour), M3 (30% of coconut pulp flour: 30% of carrot flour: 40% of wheat flour) and M4 (25% of coconut pulp flour: 35% of carrot flour: 40% of wheat flour). The results showed that the selected product based on organoleptic was the M3 formula. The nutritional value of the M3 cookies product consisting of water, protein, fat, carbohydrate and fiber contents were 3.50%, 5.52 %, 9,147%, 19,72%, 71,170% and 21,40%. Coconut pulp and carrot flour cookies had nutritional value according to standards and based on organoleptic assessment can be accepted (preferred) by panelists. Keywords: Cookies, coconut pulp flour, carrot flour. ABSTRAK Tujuan penelitian ini adalah untuk mengetahui pengaruh formulasi tepung ampas kelapa dan tepung wortel terhadap sifat organoleptik dan nilai proksimat cookies. Penelitian ini menggunakan Rancangan Acak Lengkap (RAL) dengan formulasi tepung ampas kelapa, tepung wortel dan tepung terigu yaitu M0 (100% tepung terigu), M1 (tepung ampas kelapa 40% : tepung wortel 20% : tepung terigu 40%), M2 (tepung ampas kelapa 35% : tepung wortel 25% : tepung terigu 40%), M3 (tepung ampas kelapa 30% : tepung wortel 30% : tepung terigu 40%) dan M4 (tepung ampas kelapa 25% : tepung wortel 35% : tepung terigu 40. Hasil penelitian menunjukkan bahwa produk terpilih berdasarkan organoleptik adalah formula M3. Nilai gizi dari produk cookies M3 yang terdiri dari kadar air kadar abu protein kadar lemak kadar karbohidrat dan kadar serat berturut-turut sebesar 3,50%, 5,52%, 9,147%, 19,72%, 71,170% dan 21,40%. Cookies tepung ampas kelapa dan wortel memiliki nilai gizi sesuai standar dan berdasarkan penilaian organoleptik dapat diterima (disukai) oleh panelis. Kata kunci: Cookies, tepung ampas kelapa, tepung wortel. PENDAHULUAN